A Forest‐Based Triboelectric Energy Harvester. Issue 10 (7th August 2022) - Edberg, Jesper; Mulla, Mohammad Yusuf; Hosseinaei, Omid; Alvi, Naveed ul Hassan; Beni, Valerio
Abstract: Triboelectric nanogenerators (TENGs) are a new class of energy harvesting devices that have the potential to become a dominating technology for producing renewable energy. The versatility of their designs allows TENGs to harvest mechanical energy from sources like wind and water. Currently used renewable energy technologies have a restricted number of materials from which they can be constructed, such as metals, plastics, semiconductors, and rare‐earth metals. These materials are all non‐renewable in themselves as they require mining/drilling and are difficult to recycle at end of life. TENGs on the other hand can be built from a large repertoire of materials, including materials from bio‐based sources. Here, a TENG constructed fully from wood‐derived materials like lignin, cellulose, paper, and cardboard, thus making it 100% green, recyclable, and even biodegradable, is demonstrated. The device can produce a maximum voltage, current, and power of 232 V, 17 mA m –2, and 1.6 W m –2, respectively, which is enough to power electronic systems and charge 6.5 µF capacitors. Finally, the device is used in a smart package application as a self‐powered impact sensor. The work shows the feasibility of producing renewable energy technologies that are sustainable both with respect to their energy sources and their material composition. Abstract : A triboelectric energy harvester based solely on renewable forest‐derived materials (forest‐based triboelectric nanogenerator, F‐TENG) is demonstrated for the first time. The F‐TENG shows performance comparable or superior to those previously reported for TENGs only partially based on biopolymers. The suitability of the F‐TENG technology as a self‐powered impact sensor is reported.